Reconciling insurance with market discipline: a blueprint for a European fiscal union - Dolls, Mathias; Fuest, Clemens; Heinemann, Friedrich; Peichl, Andreas (CESifo economic studies, 2016)
This contribution develops a blueprint for a European fiscal union. We argue that a viable European fiscal union can be constructed without joint liability for public debt or a centralized government with a large common budget. Such a fiscal union should combine elements of market discipline with stabilization in case of asymmetric shocks. Our proposal addresses the shortcomings of most other reform designs, which fail to offer a solution for insolvent or non-cooperative euro countries. We suggest a design which combines limited fiscal insurance with an orderly procedure to restructure the debt of insolvent member states. We show that fiscal insurance and a sovereign insolvency procedure are no contradiction but, on the contrary, are mutually reinforcing. Effective fiscal insurance helps to limit the stability risks involved in the implementation of an insolvency regime for sovereigns. And vice versa, a well-defined insolvency procedure reduces the risk that a fiscal capacity motivated as an insurance against transitory asymmetric shocks degenerates into a permanent transfer system. Moreover, we show that both elements promote the functioning of the European banking union and the new European fiscal governance.
Gesehen am 22.08.2019